Security and Privacy in Communication Networks 9th International ICST Conference, SecureComm 2013, Revised Selected Papers - Zia, Tanveer.; Zia, Tanveer.; Zomaya, Albert.; Zomaya, Albert.; Varadharajan, Vijay.; Varadharajan, Vijay.; Mao, Morley.; Mao, Morley. (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering, 2013)
This book constitutes the thoroughly refereed post-conference proceedings of the 9th International ICST Conference on Security and Privacy in Communication Networks, held in Sydney, Australia, in September 2013. The 26 revised full papers presented were carefully reviewed and selected from 70 submissions. The papers are grouped in topical sections on: security and privacy in mobile, sensor, and ad hoc networks; malware, botnets, and distributed denial of service; security for emerging technologies: VoIP, peer-to-peer, and cloud computing; encryption and key management; security in software and machine learning; network and system security model; security and privacy in pervasive and ubiquitous computing.